Anti-Parkinson Activity of Petroleum Ether Extract of Ficus religiosa (L.) Leaves - Jitendra O. Bhangale; Sanjeev R. Acharya (Hindawi Limited, 2016)
In the present study, we evaluated anti-Parkinson's activity of petroleum ether extract of Ficus religiosa (PEFRE) leaves in haloperidol and 6 hydroxydopamine (6-OHDA) induced experimental animal models. In this study, effects of Ficus religiosa (100, 200, and 400 mg/kg, p.o.) were studied using in vivo behavioral parameters like catalepsy, muscle rigidity, and locomotor activity and its effects on neurochemical parameters (MDA, CAT, SOD, and GSH) in rats. The experiment was designed by giving haloperidol to induce catalepsy and 6-OHDA to induce Parkinson's disease-like symptoms. The increased cataleptic scores (induced by haloperidol) were significantly (p<0.001) found to be reduced, with the PEFRE at a dose of 200 and 400 mg/kg (p.o.). 6-OHDA significantly induced motor dysfunction (muscle rigidity and hypolocomotion). 6-OHDA administration showed significant increase in lipid peroxidation level and depleted superoxide dismutase, catalase, and reduced glutathione level. Daily administration of PEFRE (400 mg/kg) significantly improved motor performance and also significantly attenuated oxidative damage. Thus, the study proved that Ficus religiosa treatment significantly attenuated the motor defects and also protected the brain from oxidative stress.